Basics creative design 01 Design principles - Webb, Jeremy (London Bloomsbury Publishing Plc, 2018)
"Basics Creative Photography titles are designed to provide visual arts students with a theoretical and practical exploration of each of the fundamental topics within the discipline of creative photography. Packed with examples from students and professionals and fully illustrated with clear diagrams and inspiring imagery, they offer an essential exploration of the subject. Design Principles introduces students to the use of design methodology in the creation of photographic images. In an age over saturated with photographic imagery, this book demonstrates how design awareness can add a new level of depth to your images. It guides students through a comprehensive range of principles traditionally associated with design, including the use of line, shape, color, space, texture, and light, and demonstrates how these can be applied to photography. Basics Creative Photography: Design Principles introduces students to a more considered approach that can add dynamism and impact to photography, whatever the style or genre."
Includes bibliographical references (pages 178-179) and index.
Keywords: Photography; Photography, Artistic